Pharmaceutical compositions and methods for enhancing solubility of poorly dissolved active pharmaceutical ingredients

By using polyvinyl alcohol with hydrolysis and viscosity in a specific range as a pharmaceutical excipient in the selective laser sintering method, the problem of insufficient bioavailability and stability of pharmaceutical dosage forms in the prior art is solved, and the rapid API is achieved Release and long-term stability.

CN119486718APending Publication Date: 2025-02-18MERCK PATENT GMBH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380051839.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-11-17
Filing Date
2023-07-03
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

In the prior art, there is little experience in using polyvinyl alcohol as a pharmaceutical excipient in selective laser sintering methods, and the applicability of different PVA grades is not yet clear, resulting in insufficient bioavailability and stability of the pharmaceutical dosage form.

Method used

Pharmaceutical dosage forms were produced by selective laser sintering technology using polyvinyl alcohol with a hydrolysis degree of 70% to 90% and a viscosity of 3 mPas to 8 mPas at 20°C as the component of the sintered powder.

Benefits of technology

The rapid release and improved amorphization of APIs in pharmaceutical dosage forms are achieved, ensuring the release and supersaturation of APIs are stabilized, and the bioavailability of APIs is improved, making it stable in the gastrointestinal environment for a long time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005227766270000131
    Figure BDA0005227766270000131
  • Figure BDA0005227766270000132
    Figure BDA0005227766270000132
  • Figure BDA0005227766270000141
    Figure BDA0005227766270000141
Patent Text Reader

Abstract

The present disclosure generally relates to the use of polyvinyl alcohol (PVA) in additive manufacturing technology and technology. More specifically, the present disclosure relates to the use of PVA for additive manufacturing of objects, particularly pharmaceutical dosage forms, in selective laser sintering (SLS) processes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure generally relates to the use of polyvinyl alcohol (PVA) in additive manufacturing technologies and techniques. More specifically, the present disclosure relates to the use of PVA in a selective laser sintering (SLS) process for additive manufacturing of objects, particularly pharmaceutical dosage forms. Background Art

[0002] The use of hydrophilic polymers such as polyvinyl alcohol as excipients for pharmaceutical compositions has been widely described. WO 2018 / 083285 A1 discloses powdered PVA with improved properties as a polymer matrix in pharmaceutical compositions comprising active ingredients, in particular in compressed tablets forming amorphous solid dispersions with poorly soluble active pharmaceutical ingredients (APIs).

[0003] Polyvinyl alcohol is used in amorphous solid dispersions, which is a well-known strategy to improve the bioavailability of poorly water-soluble drug substances. Although amorphous forms show high solubility, they are quite unstable and tend to recrystallize and precipitate immediately after dissolution or during changes in pH from the acidic stomach environment to the more neutral intestine. The recrystallized portion of the API cannot be absorbed. Since drug absorption occurs primarily in the intestine, pharmaceutical formulations that cannot maintain high concentrations of API in intestinal solutions usually only produce a slight increase in bioavailability. Unexpected recrystallization reduces the bioavailability of the API instead. Poor bioavailability is a significant problem encountered in the development of pharmaceutical compositions, particularly pharmaceutical compositions containing APIs that are not highly water-soluble.

[0004] In J Pharm Sci. 2008; 97(12): 5198-211, polyvinyl alcohol was successfully evaluated as inhibiting crystal formation of model compounds such as caffeine. The PVA grade used for these data is described as polyvinyl alcohol (PVA) with an average molecular weight of 47,000. Overhoff et al. Effect of Stabilizer on the Maximum Degree and Extent of Supersaturation and Oral Absorption of Tacrolimus Made By Ultra-Rapid Freezing, Pharmaceutical Research. 2008; 25(1): 167-75 describes another study using PVA to increase the supersaturation state of the model compound tacrolimus. Solid dispersions were prepared by ultrafast freeze drying. The PVA grade used was described as poly(vinyl) alcohol (PVA, Mw 13,000-23,000, 87-89% hydrolysis). PVA can be successfully used as a stabilizer. deJaeghere et al. Hot-melt extrusion of polyvinyl alcohol for oral immediate release applications, Int J Pharm. 2015; 492 (1-2): 1-9 The use of polyvinyl alcohol for hot melt extrusion has been previously described. Partially hydrolyzed PVA grades were used to evaluate their use as carriers for oral immediate release dosage forms. An effect on release rate was observed, but no direct link between degree of hydrolysis and supersaturation potential was found. In Brough et al. Use of Polyvinyl Alcohol as a Solubility Enhancing Polymer for PoorlyWater-Soluble Drug Delivery (Part 1), AAPS PharmSciTech Vol. 17, No. 1, p. 176 (01.02.2016), certain PVA grades, including PVA 4-75, PVA 4-88, PVA 4-98, PVA 4-38, were studied by non-sedimentation gastric transfer dissolution method.

[0005] Selective laser sintering (SLS) is one of the most popular additive manufacturing methods, which creates three-dimensional (3D) objects layer by layer. The method applies layers of powdered material on top of each other in sequence, with each layer of powder being sintered or coalesced together with a laser according to the computer-aided drawing (CAD) geometry of the part.

[0006] SLS is a powder bed based additive manufacturing technology used to produce complex three-dimensional parts. In SLS, a rasterized laser is used to scan a bed of polymer powder, which is sintered to form a solid shape in layered form. As the laser beam scans the powder, it melts layer by layer due to the increased temperature, and the final part approaches full density and will produce the properties of bulk material (polymer). By controlling the energy input, the density of the sintered material can be controlled and parts ranging from highly porous to almost fully dense can be achieved. In theory, every thermoplastic polymer that can be converted into powder form can be processed by this technology, but the reality is that each material behaves differently during melting, coalescence and consolidation, which is often unpredictable and usually requires unique SLS processing parameters. For example, the bed temperature and laser energy input can be selected based on the processing window of the polymer's thermal profile and its energy absorption. Laser parameters can also be selected based on the particle size and shape of the powder.

[0007] There are different types of polymer particles that are commonly used in the SLS method. Semi-crystalline resins such as polyamide (including PA12, PA11 and PA6), polylactic acid (PLA), polyetheretherketone (PEEK), polyethylene (PE), polypropylene (PP), etc. are used. The most commonly used polymer powder is polyamide PA12. The common name for polyamide is nylon. For example, polyamide PA12 is also called nylon 12, and polyamide PA6 is also called nylon 6. According to the CAD geometry file of the part, a layer-by-layer structure is formed by sintering the polymer particles together with a laser above the melting point of the polymer.

[0008] Currently, there is relatively little experience using polyvinyl alcohol as a pharmaceutical excipient in selective laser sintering. In Basit et al. International Journal of Pharmaceutics 529 (2017) 285–293, Kollicoat IR, which is a copolymer of 75% polyvinyl alcohol and 25% polyethylene, was used in an SLS process with paracetamol as the active pharmaceutical ingredient. Yang et al. International Journal of Pharmaceutics 593 (2021) 120127 disclose PVA as one of several excipients for SLS printing. To date, the suitability of different PVA grades (viscosity and degree of hydrolysis) is unclear.

[0009] There remains a need for polyvinyl alcohol as a pharmaceutical excipient with improved properties for selective laser sintering processes. Summary of the invention

[0010] Surprisingly, it has been found that polyvinyl alcohol can be used in a method for selective laser sintering of sintered powders to form pharmaceutical dosage forms. It has further been found that polyvinyl alcohol having a degree of hydrolysis of 70% to 90% and a viscosity of 3 to 8 mPas as a 4% solution at 20°C is particularly suitable for selective laser sintering.

[0011] Unexpectedly, it was shown that there is an optimal range of degree of hydrolysis and viscosity, which results in a pharmaceutical dosage form with beneficial properties, such as faster API release and / or improved amorphization of the API compared to commonly used PVA grades. The PVA grade within this optimal range ensures the release and supersaturation of the API with different 3D printing parameters and stabilizes the release and supersaturation of the API with different 3D printing parameters. In addition, it has been shown that the amorphous form of the API can be stable in the pharmaceutical dosage form for a long time, for example, for more than 6 months. In a preferred embodiment, long-term stability is measured at 40°C / dry conditions, 25°C / 60% RH, 30°C / 65% RH, 30°C / 75% RH or 40°C / 75% RH for 3 months or 6 months, wherein more than 80%, 85%, 90%, 92%, 95%, 97%, 98% or 99% of the API is still present in its amorphous form.

[0012] In a preferred embodiment of the present invention, the degree of hydrolysis of the polyvinyl alcohol is 80% to 90%, and the viscosity of a 4% solution at 20° C. is 3 mPas to 4 mPas.

[0013] In another aspect, the present invention provides a method for producing a pharmaceutical dosage form by selective laser sintering of sintered powder, comprising the steps of:

[0014] (a) providing a sintered powder comprising at least one active pharmaceutical ingredient and polyvinyl alcohol, wherein the degree of hydrolysis of the polyvinyl alcohol is 70% to 90% and the viscosity of a 4% solution at 20° C. is 3 mPas to 8 mPas, and

[0015] (b) operating a selective laser sintering apparatus that selectively fuses layers of sintered powder to produce a pharmaceutical dosage form.

[0016] Another aspect of the invention relates to a sintering powder for selective laser sintering, comprising at least one active pharmaceutical ingredient and polyvinyl alcohol, wherein the degree of hydrolysis of the polyvinyl alcohol is 70% to 90% and the viscosity of a 4% solution is 3 mPas to 8 mPas at 20° C. The sintering powder may contain other excipients and / or light absorbing materials.

[0017] Another aspect of the present invention relates to a pharmaceutical dosage form obtainable by a process as described above, in particular a pharmaceutical dosage form produced by selective laser sintering of a sintered powder, wherein the sintered powder comprises at least one active pharmaceutical ingredient and polyvinyl alcohol having a degree of hydrolysis of 70% to 90% and a viscosity of a 4% solution at 20° C. of 3 to 8 mPas. DETAILED DESCRIPTION

[0018] One embodiment of the present invention is the use of polyvinyl alcohol in a method for selective laser sintering of a sintered powder to form a pharmaceutical dosage form, wherein the sintered powder comprises at least one active pharmaceutical ingredient and polyvinyl alcohol, wherein the polyvinyl alcohol has a degree of hydrolysis of 70% to 90% and a viscosity of a 4% solution at 20°C of 3 to 8 mPas.

[0019] According to the invention, selective laser sintering is a method in which a powder bed filled with a polymer-containing powder mixture is sintered and / or melted using a laser beam by scanning the laser according to a cross-section of a digital model. A polymer version of the digital model is produced in a layer-by-layer manner by laser scanning successive layers of the powder mixture.

[0020] This approach would require a selective laser sintering printer equipped with a laser source and a galvanometric system to scan the laser over the powder bed surface or an xy motion system to move the actual laser source to scan the powder bed. The printer would also have to provide a powder application system to spread the powder in layers, and some heating capability to heat the build chamber and the surface of the powder bed.

[0021] According to the present invention, the powder mixture used is prepared by mixing PVA, API and other optional pharmaceutically acceptable excipients. First, PVA is sieved through a 300 micron sieve, and the material passing through the sieve is mixed with excipients and API and mixed in a turbula mixer for 30 minutes. The resulting mixture is then sieved through a 300 micron sieve, and the material passing through the sieve is loaded into a printer.

[0022] After loading the mixture, the printer is preheated to a set temperature below the Tg of the PVA and the printing process is started. During the printing process, parameters such as chamber and print bed temperature are set to appropriate values ​​obtained through experimental studies to provide printed tablets with desired properties with respect to mechanical and morphological properties. Other parameters that affect the process are the laser energy input and the layer height of each applied layer. The laser energy input can be controlled in a variety of ways depending on the type of printer used, and is typically via adjusting the laser scanning speed, the scan line spacing (the distance between the scanning laser lines) or by adjusting the energy output of the laser.

[0023] Once the printing process is complete, the printed tablet is allowed to slowly cool in the printer and then removed and cleaned from the surrounding unsintered powder.

[0024] Polyvinyl alcohol (PVA) is a synthetic water-soluble polymer with the ideal formula [CH2CH(OH)] n . It has good film-forming, adhesive and emulsifying properties. PVA is prepared from polyvinyl acetate, in which the acetate functional groups are partially or completely hydrolyzed to alcohol functional groups. If the hydrolysis is not complete, PVA is a random copolymer composed of vinyl alcohol repeating units -[CH2CH(OH)]- and vinyl acetate repeating units -[CH2CH(OOCCH3)]-. The polarity of PVA is closely related to its molecular structure. The degree of hydrolysis and the molecular weight determine the molecular properties of PVA. With increasing degree of hydrolysis of acetate groups, the solubility of the polymer in aqueous media, as well as the crystallinity and melting temperature of the polymer, also increase. However, at high degrees of hydrolysis exceeding 88%, the solubility of PVA decreases again. PVA is generally soluble in water, but is almost insoluble in almost all organic solvents, with the exception of ethanol in some cases.

[0025] Typical PVA nomenclature indicates the viscosity of the polymer as a 4% solution at 20°C and the degree of hydrolysis. For example, PVA 3-83 is a PVA grade with a viscosity of 3 mPas and being 83% hydrolyzed, i.e. having 83% vinyl alcohol repeating units and 17% vinyl acetate repeating units. The skilled person knows that, according to the common rounding method, an 83% hydrolysis grade and a viscosity of 3 mPas encompasses a calculated hydrolysis grade of 82.50% to 83.49% and a calculated viscosity of 2.50 mPas to 3.49 mPas%. The viscosity according to the invention is measured as described in USP 39 under the monograph "Polyvinyl Alcohol" using the method viscosity rotation method (912).

[0026] The degree of hydrolysis according to the invention is measured by determining the saponification value of the polyvinyl alcohol, for example as described in USP 39 under the monograph "Polyvinyl alcohol" under "Degree of hydrolysis":

[0027] Sample: 1g polyvinyl alcohol, pre-dried at 110° to constant weight

[0028] analyze:

[0029] Transfer the sample to a wide-mouth, 250 ml conical flask and attach it to a reflux condenser via a suitable glass joint. Add 35 ml of dilute methanol (3 parts out of 5) and mix gently to ensure complete wetting of the solid. Add 3 drops of phenolphthalein TS and neutralize with 0.2 N hydrochloric acid or 0.2 N sodium hydroxide if necessary. Add 25.0 ml of 0.2 N sodium hydroxide VS and reflux gently on a hot plate for 1 hour. Wash the condenser with 10 ml of water, collect the washings in a flask, cool, and titrate with 0.2 N hydrochloric acid VS. Simultaneously carry out a blank determination in the same manner using the same amount of 0.2 N sodium hydroxide VS.

[0030] Calculation of saponification value:

[0031] Calculate the saponification value:

[0032] Result = [(V B -V S )x N x M r ] / W

[0033] V B = 0.2N hydrochloric acid consumed in blank titration VS volume (ml)

[0034] V S = 0.2N hydrochloric acid consumed when titrating the sample solution VS volume (ml)

[0035] N = actual equivalent concentration of hydrochloric acid VS

[0036] M r = molecular weight of potassium hydroxide, 56.11

[0037] W = weight of the polyvinyl alcohol portion taken (g)

[0038] Calculation of degree of hydrolysis:

[0039] Calculate the degree of hydrolysis, expressed as the percentage of polyvinyl acetate hydrolysis:

[0040] Result = 100 - [7.84x S / (100 - 0.075x S))

[0041] S = saponification value of polyvinyl alcohol

[0042] The use of the PVA grades according to the invention is of interest for the formulation of solid oral pharmaceutical dosage forms with immediate, immediate or prolonged API release.

[0043] The preferred PVA has a degree of hydrolysis of 70% to 90% and a viscosity of 3 to 5 mPas at 20°C for a 4% solution, more preferably 3 to 4 mPas at 20°C, and most preferably 4 mPas at 20°C.

[0044] In another embodiment of the present invention, the degree of hydrolysis of the polyvinyl alcohol is 70% to 90%, preferably 80% to 90%, and the viscosity is as described above.

[0045] In another embodiment of the invention, the polyvinyl alcohol has a degree of hydrolysis of 80% to 90% and a viscosity of 3 mPas as a 4% solution at 20°C, or has a degree of hydrolysis of 80% to 90% and a viscosity of 4 mPas as a 4% solution at 20°C.

[0046] In another embodiment of the present invention, the polyvinyl alcohol is PVA 3-80, PVA 3-82, PVA 4-88 or PVA 5-74, preferably PVA 3-80, PVA 3-82 or PVA 4-88, more preferably PVA 4-88.

[0047] In another embodiment of the present invention, the polyvinyl alcohol is PVA 3-82, PVA 4-88 or PVA 5-74, more preferably PVA 3-82 or PVA 4-88, most preferably PVA 3-82.

[0048] The above embodiments for API and / or PVA grades also apply to the use of polyvinyl alcohol in a method for selective laser sintering of a sintered powder, a method for producing a pharmaceutical dosage form by selective laser sintering of a sintered powder, a sintered powder for selective laser sintering, and a pharmaceutical dosage form produced by selective laser sintering of a sintered powder as described above.

[0049] Another embodiment of the present invention is a sintering powder for selective laser sintering, comprising at least one active pharmaceutical ingredient and polyvinyl alcohol having a degree of hydrolysis of 70% to 90% and a viscosity of 4% solution at 20° C. of 3 to 8 mPas.

[0050] For the avoidance of doubt, the method according to the present invention comprises selective laser sintering using any PVA, PVA specification or PVA grade as defined below.

[0051] In another embodiment of the present invention, the sintered powder and the pharmaceutical dosage form may contain other pharmaceutically acceptable excipients. Pharmaceutically acceptable excipients include flow control agents such as silicon dioxide, fillers, plasticizers, surfactants, light absorbing materials such as ruby ​​red or Candurin pigments, and other suitable components well known to those skilled in the art.

[0052] Depending on the wavelength of light emitted by the laser, a light absorbing material (pigment) may be needed that absorbs light at the emitted wavelength. These light absorbing materials may contain transition metals that absorb at about 450nm or a wider range of carbons covering the visible and near IR range. Light absorption is the process by which light is absorbed and converted into energy. Heat is generated when light is absorbed. Therefore, selective absorption of light by a particular material occurs because the frequency of the light wave matches the frequency of the electron vibrations in the atoms of that material.

[0053] The light absorbing materials are all materials suitable for the SLS method as described above and are known to those skilled in the art. Preferably, light absorbing materials that have been proven to work under 455 nm laser irradiation are used, such as Candurin NXT, Ruby Red, Candurin Gold Sheen, Aluminum Lake, activated carbon (also working at 808 nm) or iron oxide (Fe2O3). More preferably, Ruby Red is used.

[0054] CO2 lasers emitting at about 10 microns do not usually require the addition of light absorbing materials because the CH bonds absorb energy at that wavelength and this type of bond can be found in most polymers.

[0055] For the avoidance of doubt, other pharmaceutically acceptable excipients as defined above are not required according to the beneficial properties of the present invention. However, those excipients may be used for other purposes, such as to optimize the manufacturing process of the pharmaceutical composition or oral dosage form according to the present invention.

[0056] Furthermore, the pharmaceutical composition according to the present invention may comprise additional pharmaceutically acceptable hydrophilic or lipophilic polymers.

[0057] In a preferred embodiment, the sintered powder further comprises a light absorbing material.

[0058] As used herein, the phrase "pharmaceutically acceptable" refers to all excipients, polymers, compounds, solvents, dispersion media, flow control agents, carriers, coatings, active agents, isotonic agents and absorption delaying agents, etc., which do not produce allergic or similar adverse reactions when generally administered to humans. The use of such materials in pharmaceutical compositions is well known in the art.

[0059] In a preferred embodiment, the particle size of the sintered powder has a D50 of 200 μm or less. Preferably, the particle size (D50) of the sintered powder is between 20 μm and 200 μm, 20 μm and 150 μm, or 20 μm and 100 μm.

[0060] In a preferred embodiment, the particle size of PVA has a D50 of 200 μm or less. Preferably, the particle size (D50) of PVA is between 20 μm and 200 μm, 20 μm and 150 μm, or 20 μm and 100 μm.

[0061] In another preferred embodiment, the particle size of PVA has a D90 of 250 μm or less. Preferably, the particle size (D90) of PVA is between 100 μm and 250 μm, more preferably between 140 μm and 220 μm.

[0062] Another embodiment of the present invention is a method for producing a pharmaceutical dosage form by selective laser sintering of sintered powder, comprising the steps of:

[0063] (a) providing a sintered powder comprising at least one active pharmaceutical ingredient and polyvinyl alcohol, wherein the degree of hydrolysis of the polyvinyl alcohol is 70% to 90% and the viscosity of a 4% solution at 20° C. is 3 mPas to 8 mPas, and

[0064] (b) operating a selective laser sintering apparatus that selectively fuses layers of sintered powder to produce a pharmaceutical dosage form.

[0065] For the avoidance of doubt, the method according to the present invention comprises selective laser sintering using any PVA, PVA specification or PVA grade as defined below.

[0066] Another embodiment of the present invention is a pharmaceutical dosage form obtainable by the method for producing a pharmaceutical dosage form by selective laser sintering of a sintered powder as described above.

[0067] In another embodiment, the pharmaceutical dosage form is produced by selective laser sintering of a sintered powder, wherein the sintered powder comprises at least one active pharmaceutical ingredient and polyvinyl alcohol having a degree of hydrolysis of 70% to 90% and a viscosity of a 4% solution at 20° C. of 3 to 8 mPas.

[0068] For the avoidance of doubt, pharmaceutical dosage forms according to the present invention include pharmaceutical dosage forms having any PVA, PVA strength or PVA grade as defined below.

[0069] The API is a bioactive agent. The API can be a small molecule in the form of a weak base, weak acid or neutral molecule, and can be in the form of one or more pharmaceutically acceptable salts, esters, derivatives, analogs, prodrugs and solvates thereof. The sintered powder and pharmaceutical dosage form can include more than one API. In one embodiment, the API is a poorly soluble or lipophilic API.

[0070] As used herein, the terms "poorly soluble API", "poorly water soluble API" and "lipophilic API" refer to an API having a solubility such that the highest therapeutic dose of the particular API administered to an individual cannot be dissolved in 250 ml of an aqueous medium having a pH range of 1 to 8, as defined by low solubility according to Biopharmaceutical Classification System (BCS) Classes 2 and 4. Poorly soluble APIs having weakly basic or weakly acidic characteristics have a pH-dependent solubility profile and can have a wide range of solubility in the aqueous environment of the gastrointestinal tract. APIs falling into BCS Classes 2 or 4, respectively, are well known to those skilled in the art.

[0071] In one embodiment, the API is a weakly basic API. As used herein, the term "weakly basic API" refers to a basic active pharmaceutical ingredient (API), wherein the basic API is not completely ionized in water.

[0072] At least one active pharmaceutical ingredient (API) according to the present invention may be dispersed in polyvinyl alcohol to form an amorphous solid dispersion.

[0073] Another embodiment of the present invention is the use of polyvinyl alcohol in a method for selective laser sintering of sintered powders to form a pharmaceutical dosage form, wherein an amorphous solid dispersion of at least one active pharmaceutical ingredient in polyvinyl alcohol is formed, and wherein the degree of hydrolysis of the polyvinyl alcohol is from 70% to 90% and the viscosity of a 4% solution at 20°C is from 3 mPas to 8 mPas.

[0074] As used herein, the term "amorphous solid dispersion" is a dispersion of at least one amorphous API in a polymer matrix. Preferably, the amorphous API is distributed in the polymer matrix in a molecularly dispersed state. In this case, the solid dispersion is a solid solution. Upon dissolution, a formulation containing an amorphous solid dispersion can achieve a higher solubility in an aqueous medium than a crystalline API.

[0075] The API included in the pharmaceutical dosage form of the present invention has a sufficient therapeutically effective amount. For a given API, the therapeutically effective amount is generally known or readily available to those skilled in the art. Typically, the API can be present in the pharmaceutical dosage form at a weight ratio of API to polyvinyl alcohol of 0.1:99.1 to 60:40, preferably 1:99 to 50:50, more preferably 5:95 to 40:60, and most preferably 10:90 to 30:70.

[0076] It was found that PVA having a degree of hydrolysis and a viscosity within the above ranges shows surprisingly good performance when used in a process for selective laser sintering of a sintered powder to form a pharmaceutical dosage form comprising an active pharmaceutical ingredient, compared to PVA outside of the above ranges.

[0077] It has been unexpectedly found that selective laser sintering of a sintered powder comprising an active pharmaceutical ingredient and PVA having the above-identified viscosity and hydrolysis grade results in a pharmaceutical dosage form

[0078] Show faster and higher API releases, and

[0079] • Improved amorphization with API.

[0080] When comparing the powder X-ray diffraction (PXRD) data and / or differential scanning calorimetry (DSC) data with the pharmaceutical dosage forms manufactured by SLS printing with PVA outside the above ranges under the same process conditions, it can be seen that the amorphization of the pharmaceutical dosage forms manufactured by SLS printing with PVA having a degree of hydrolysis and a viscosity within the above ranges is improved. The preferred PVA is a polyvinyl alcohol having a degree of hydrolysis of 70% to 90% and a viscosity of 3 mPas to 8 mPas of a 4% solution at 20°C, more preferably a polyvinyl alcohol having a degree of hydrolysis of 80% to 90% and a viscosity of 3 mPas to 4 mPas of a 4% solution at 20°C. The preferred PVA grades are PVA3-80, PVA 3-82, PVA 4-88 or PVA 5-74. The best amorphization results have been demonstrated with PVA 4-88 and PVA 3-82, preferably PVA 4-88.

[0081] In addition, the PVA having the above-determined viscosity and hydrolysis grade ensures the release and supersaturation of API (especially poorly soluble API) in aqueous media and stabilizes the release and supersaturation of API (especially poorly soluble API) in aqueous media, thereby preventing crystallization and phase separation. Since the low water solubility of API is usually accompanied by its low bioavailability after administration in a pharmaceutical formulation, the composition of the present invention also helps to improve the bioavailability of poorly water-soluble API (especially weakly basic API).

[0082] It has been shown that pharmaceutical dosage forms made by SLS printing with PVA having a degree of hydrolysis and viscosity within the above ranges have significantly faster and more pronounced API release. Dissolution experiments have demonstrated that the PVA grades of the present invention, such as PVA 3-82, PVA 5-74 and PVA 4-

[0083] 88, is particularly suitable as a polymer for this purpose. Compared with other PVA grades, PVA 3-82 has the highest API release ( Fig.23 ), and provide enhanced solubility compared to the crystalline form of indomethacin. This is particularly surprising because this result could not be expected from the PXRD and / or DSC data.

[0084] Furthermore, the PVA with the above determined viscosity and hydrolysis grade has an improved surface quality and a smooth surface finish, which can be seen with a scanning electron microscope (SEM) method. They differ in surface area, which can be measured by BET (gas adsorption), tablet hardness and porosity, which can be measured by μCT measurement.

[0085] PVA having the above identified viscosity and hydrolysis grade further exhibits improved API stability.

[0086] As used herein, "bioavailability" is a term referring to the extent to which an API becomes available to target tissues after administration to a patient's body.

[0087] After dissolving the pharmaceutical dosage form of the present invention, improved supersaturation is observed and the API is better maintained in solution. In addition, during the sintering process, the API can be better incorporated into the PVA matrix.

[0088] After entering the gastrointestinal tract, the pharmaceutical dosage form swells and disintegrates in the aqueous environment of the gastrointestinal fluid, thereby releasing the API. Although the salt form of the weakly basic API can show an improved initial aqueous concentration in acidic gastric fluid, the weakly basic API is rapidly converted to the free base form in the more neutral intestinal fluid, where the free base form of the API has a significantly lower equilibrium concentration. Compared with commonly used PVA, the PVA according to the present invention maintains enhanced API concentrations in model solutions that simulate acidic and neutral gastrointestinal solutions. Therefore, the pharmaceutical dosage form according to the present invention has the potential to provide enhanced bioavailability for poorly soluble APIs. The solubility-improved form of the API in the presence of the PVA grade according to the present invention provides a concentration of the API in gastric fluid or simulated gastric fluid that is greater than the API concentration provided in the presence of the commonly used PVA grade.

[0089] Example:

[0090] Example 1: SLS printing using PVA 4-88

[0091] Preparation of powder formulations

[0092] Indomethacin loaded powder formulations were prepared according to Table 1. All powder mixtures were sieved using a 315 μm stainless steel test sieve (VWR International AB, Sweden) and mixed using a Turbula oscillator (Turbula T2F oscillator, Glen Mills, Inc., Clifton, NJ, US) for 15 minutes. Candurin Ruby Red and colloidal silicon dioxide (Aerosil) were added to the formulation to enhance the laser energy absorption of the powder and improve the powder flowability during the layer application process, respectively. PVA 4-88 was used. MXP (Merck KGaA) was used as the polyvinyl alcohol. Formulations were prepared in large enough batches (approximately 1500 mL) to partially fill the build volume (100 x 100 x 100 mm) of a Sintratec Kit SLS 3D printer (Sintratec, Brugg, Switzerland).

[0093] Table 1. Composition of the prepared powder formulations

[0094] preparation PVA 4-88 Ruby Red Aerosil Indomethacin wt.% 88.5 0.5 1 10

[0095] Selective Laser Sintering 3D Printing of Dosage Forms

[0096] The tablet template was created and designed in Solidworks 2019SP05 ( Figure 1 ), and the obtained standard triangular language file (STL file) was subsequently prepared for printing in the Sintratec software using the method parameters presented in Table 2. The energy density was calculated according to the following equation:

[0097]

[0098] P—laser power (2.3 W); HS—scanning line spacing (0.05 mm); V—scanning speed (mm / s); α—absorptivity of powder (the coefficient of absorption at 455 nm for each powder type should be measured / calculated).

[0099] Table 2. Method parameters used for each formulation

[0100]

[0101]

[0102] Figure 1 A schematic diagram and a 3D model of a tablet (4 x 9.5 mm) are shown.

[0103] The 3D printing process was further carried out as follows: the prepared powder formulation (Table 1) was placed and packed into the powder reservoir platform (100x 100x 100mm) of the SLS 3D printer. A thin layer of the formulation was then spread onto the build platform, and the powder bed was then slowly heated to the temperature specified in Table 2. The sintering process was performed in a layer-by-layer manner using a 2.3W diode (λ = 455nm) according to the model given in the STL file. A total of 36 tablets were printed per batch, laid flat on the build platform, using a 125μm layer height. Specific values ​​of the laser scanning speed were selected when printing different batches, and each speed was used at three different print bed temperatures. At the end of the printing process, the finished batch was collected from the build platform by sieving. The tablets were additionally dusted using compressed air to remove excess powder and stored in a sealed container for further analysis.

[0104] Characterization of powder formulations and 3D printed dosage forms

[0105] Using Cu-Kα 1,2 Powder X-ray diffraction (PXRD) diffractograms of the original and heat-treated powder formulations and printed dosage forms were collected on a Bruker D8 Advance TwinTwin diffractometer (Bremen, Germany). The instrument was operated at 40 mA and 40 kV, using a 0.02° step size and a data collection time of 1 h. A 10 °C min -1 Differential scanning calorimetry (DSC) thermograms were obtained with heating and cooling rates of 200 ° C and nitrogen as purge gas. Repeated heating-cooling measurements were performed from -40 to 200 ° C and from 200 to 10 ° C in the first cycle and from 10 to 200 ° C in the next cycle. The size (n = 10) and weight (n = 30) of the printed tablets were checked using a digital caliper and an analytical balance (Mettler Toledo XS 64 analytical balance, Schwerzenbach, Switzerland). According to the European Pharmacopoeia (edition 10.0), the friability test was performed on about 6.5 g tablets at 25 rpm and 100 turns using a Pharmatest PTF E friability tester (Hainberg, Germany). The tablets were carefully weighed before and after the measurement, and the total weight loss (i.e., friability) of the tablets was calculated.

[0106] Figure 2 Method parameters and characteristics of 3D printed dosage forms are shown.

[0107] Batches printed at 75 °C and 300 mm / s retained crystalline API traces, while 200 mm / s produced completely amorphous API.

[0108] In the figures, PVA 4-88 is referred to as Parteck MXP.

[0109] Figure 3 Shown is the DSC thermogram of a batch printed with PVA 4-88 at 75 °C.

[0110] Figure 4 The diffraction pattern of a batch printed at 75°C with indomethacin and PVA 4-88 is shown (the numbers in brackets reflect the batch number).

[0111] Batches retained crystalline API traces printed at 100 °C and 300 and 400 mm / s, while 200 mm / s produced completely amorphous API.

[0112] Figure 5 Shown is the DSC thermogram of a batch printed with PVA 4-88 at 100 °C.

[0113] Figure 6 The diffraction pattern of a batch printed at 100°C with indomethacin and PVA 4-88 is shown (the numbers in brackets reflect the batch number).

[0114] Batches printed at 125 °C and 400 mm / s retained crystalline API traces, while 200 and 300 mm / s produced completely amorphous API.

[0115] Figure 7 Shown is the DSC thermogram of a batch printed with PVA 4-88 at 125 °C.

[0116] Figure 8 The diffraction pattern of a batch printed at 125°C with indomethacin and PVA 4-88 is shown (the numbers in brackets reflect the batch number).

[0117] Example 2: SLS printing using PVA 3-82

[0118] The preparation of the powder formulation was performed according to Example 1. PVA3-82 was used as polyvinyl alcohol. Selective laser sintering 3D printing of the dosage form was performed according to Example 1. For Example 2, a layer height of 150 μm was used.

[0119] Characterization of powder formulations and 3D printed dosage forms

[0120] The characterization methods of powder formulations and 3D printed dosage forms were performed as described in Example 1.

[0121] Fig. 9 Method parameters and characteristics of 3D printed dosage forms are shown.

[0122] Batches printed at 75 °C and 300 mm / s retained crystalline API traces, while 200 mm / s produced completely amorphous API.

[0123] In the figures, PVA 3-82 is referred to as polymer 1.

[0124] Fig.10 Shown is the DSC thermogram of a batch printed with PVA 3-82 at 75 °C.

[0125] Fig.11 The diffraction pattern of a batch printed at 75°C with indomethacin and PVA 3-82 is shown (the numbers in brackets reflect the batch number).

[0126] Batches retained crystalline API traces printed at 100 °C and 300 and 400 mm / s, while 200 mm / s produced completely amorphous API.

[0127] Fig.12 Shown is the DSC thermogram of a batch printed with PVA 3-82 at 100 °C.

[0128] Fig.13 The diffraction pattern of a batch printed at 100°C with indomethacin and PVA 3-82 is shown (the numbers in brackets reflect the batch number).

[0129] Batches printed at 125 °C and 400 mm / s retained crystalline API traces, while 200 and 300 mm / s produced completely amorphous API.

[0130] Fig.14 Shown is the DSC thermogram of a batch printed with PVA 3-82 at 125 °C.

[0131] Fig.15 Shown is the diffraction pattern of a batch printed at 125°C with indomethacin (the number in brackets reflects the batch number) and PVA 3-82.

[0132] Example 3: SLS printing using PVA 5-74

[0133] The preparation of the powder formulation was performed according to Example 1. PVA 5-74 was used as polyvinyl alcohol. Selective laser sintering 3D printing of the dosage form was performed according to Example 1. For Example 3, a layer height of 150 μm was used.

[0134] Characterization of powder formulations and 3D printed dosage forms

[0135] The characterization methods of powder formulations and 3D printed dosage forms were performed as described in Example 1.

[0136] Fig.16 Method parameters and characteristics of 3D printed dosage forms are shown.

[0137] Batches of retained crystalline API traces were printed at 75°C and 200 mm / s.

[0138] In the figures, PVA 5-74 is referred to as polymer 2.

[0139] Fig.17 Shown is the DSC thermogram of a batch printed with PVA 5-74 at 75°C and 200 mm / s.

[0140] Fig.18 The diffraction pattern of a batch printed at 75°C (200 mm / s) with indomethacin and PVA 5-74 is shown.

[0141] All batches printed at 100°C retained crystalline API traces. However, for batches printed at 300 mm / s and 400 mm / s, the DSC and XRD results did not match. The size of the API peak on the DSC did not correspond to the number of API characterizing peaks in the XRD results.

[0142] Fig.19 Shown is the DSC thermogram of a batch printed with PVA 5-74 at 100 °C.

[0143] Fig. 20 The diffraction pattern of a batch printed at 100°C with indomethacin and PVA 5-74 is shown (the numbers in brackets reflect the batch number).

[0144] The batch printed at 125°C and 400 mm / s retained a crystalline API trace, while 200 mm / s produced no crystallinity trace. Regarding the batch printed at 300 mm / s, there was no trace of API crystallinity according to DSC. However, in the XRD results of the batch printed at 300 mm / s, there was a small peak, which may indicate the presence of some crystallinity.

[0145] Fig.21 Shown is the DSC thermogram of a batch printed with PVA 5-74 at 125 °C.

[0146] Fig. 22 The diffraction pattern of a batch printed at 125°C with indomethacin and PVA 5-74 is shown (the numbers in brackets reflect the batch number).

[0147] Example 4: Dissolution Test

[0148] Preparation of powder formulations

[0149] Preparation of PVA 3-82 and PVA 5-74 with PVA 4-88, Kollidon in different formulations and Plasdone TM S-630 was used for selective laser sintering (SLS). Each polymer was prepared in a formulation calculated as 88.5% polymer, 1% pigment, 0.5% silica, and 10% indomethacin by weight. The formulation was prepared by weighing, manually mixing, and sieving using a 315 μm stainless steel test sieve (VWR International AB, Stockholm, Sweden). The sieved formulation was mixed again for 20 min using a Turbula oscillator (Turbula T2F oscillator, Glen Mills, Inc., Clifton, NJ, US). Pigments and colloidal silica were added to the formulation to enhance the laser energy absorption of the powder and to improve the powder flowability during the layer application process. The mixed powder was then placed in a thermostat ( The samples were heat treated overnight at 70°C in a BMT Medical Technologiesro, Brno, Czech Republic, and mixed again using a Turbula shaker.

[0150] Selective Laser Sintering 3D Printing of Dosage Forms

[0151] Prior to printing, tablets were created in Fusion 360 (student version, Autodesk, USA) and subsequently uploaded as STL files to Sintratec Central 1.2.7 (Sintratec AG, Brugg, Switzerland). Batches of 36 tablets were created and arranged in the print chamber. The following parameters were then set for all formulations: 50 μm perimeter offset, 50 μm scan line spacing, 150 μm scan line offset, and 3 perimeter paths. Sintering was performed in a layer-by-layer manner using a 2.3 W diode (λ = 455 nm) according to the template model given in the STL file. The tablets were printed flat on the build platform, and for Kollidon A layer height of 150 μm was used, and for all other polymers, 125 μm. Specific values ​​of laser scan speed were selected when printing different batches, and each speed was used at three different printing temperatures. Batches created with PVA 3-82, PVA 5-74, and PVA 4-88 were printed at 75, 100, and 125 °C, while batches created with Kollidon and Plasdone TMThe batches created by the S-630 were printed at 75, 100 and 112.5 °C. For the laser scanning speed, the three selected speeds were 200, 300 and 400 mm / s. At the end of the printing process, the finished batches were collected from the build platform by sieving. The tablets were additionally dusted using compressed air to remove excess powder and stored in a sealed container for further analysis.

[0152] Dissolution test

[0153] The dissolution test was performed using a Sotax AT7 intelligent dissolution tester (Aesch, Switzerland). At 37±0.5°C and 50rpm, the tablets were precipitated in 500mL simulated gastric fluid (SGF: 800mL 1M HCl, 20g NaCl ad10L, pH 1.2) using a sedimentation aid to perform in vitro drug release distribution on 3D printed tablets (n=3). The drug concentration in the dissolution medium was determined by high performance liquid chromatography (HPLC) (Agilent 1260Infinity II, Agilent Technologies, Inc., Santa Clara, USA) on a 10μL filtered sample (0.45μm PTFE filter, VWR International GmbH). The HPLC determination was performed using acetonitrile and phosphate buffer (0.01M NaH2PO*H2O 1,38g / L+0.01M Na2HPO4 1,41g / L) with a mobile phase composition in a ratio of 1:1. At 40°C at 1mL min -1 The samples were injected into a Supelcosil LC-18 column (30 x 4 mm, 5 μm) at a flow rate of 1.5 % and the eluent was analyzed at 254 nm. These dissolution tests were performed on the batches with the best characteristics for each polymer in terms of weight distribution, PXRD, DSC and friability. For PVA 3-82, PVA 5-74 and PVA 4-88, these were batches printed at 125°C and 200 mm / s. For Kollidon and Plasdone TM S-630, these are the batches printed at 112.5°C and 200m / s.

[0154] Fig.23 Dissolution results for the best batch in the drug loading test for each formulation are shown.

Claims

1. Use of polyvinyl alcohol in a method for selective laser sintering of a sintered powder to form a pharmaceutical dosage form, wherein the sintered powder comprises at least one active pharmaceutical ingredient and polyvinyl alcohol, the polyvinyl alcohol having a degree of hydrolysis of 70% to 90% and a viscosity of a 4% solution at 20° C. of 3 to 8 mPas.

2. The use according to claim 1, wherein the degree of hydrolysis of the polyvinyl alcohol is 80% to 90%, and the viscosity of a 4% solution at 20°C is 3 mPas to 4 mPas.

3. The use according to claim 1 or 2, wherein the polyvinyl alcohol is PVA 3-80, PVA 3-82, PVA 4-88 or PVA 5-74.

4. The use according to any one of claims 1 to 3, wherein the sintered powder further comprises at least one light absorbing material.

5. A method for producing a pharmaceutical dosage form by selective laser sintering of sintered powder, comprising the steps of: (a) providing a sintered powder comprising at least one active pharmaceutical ingredient and polyvinyl alcohol, wherein the degree of hydrolysis of the polyvinyl alcohol is 70% to 90% and the viscosity of a 4% solution at 20° C. is 3 mPas to 8 mPas, and (b) operating a selective laser sintering apparatus that selectively fuses layers of sintered powder to produce a pharmaceutical dosage form. 6 . The method according to claim 5 , wherein the degree of hydrolysis of the polyvinyl alcohol is 80% to 90%, and the viscosity of a 4% solution at 20° C. is 3 mPas to 4 mPas.

7. The method according to claim 5 or 6, wherein the sintered powder further comprises at least one light absorbing material.

8. The method according to any one of claims 5 to 7, wherein the particle size of the sintered powder has a D50 of 200 μm or less.

9. A sintering powder for selective laser sintering, comprising at least one active pharmaceutical ingredient and polyvinyl alcohol, wherein the degree of hydrolysis of the polyvinyl alcohol is 70% to 90% and the viscosity of a 4% solution at 20°C is 3 mPas to 8 mPas. 10 . The sintered powder according to claim 9 , wherein the degree of hydrolysis of the polyvinyl alcohol is 80% to 90%, and the viscosity of a 4% solution at 20° C. is 3 mPas to 4 mPas.

11. The sintered powder according to claim 9 or 10, further comprising at least one light absorbing material.

12. A pharmaceutical dosage form obtainable by the process according to any one of claims 5 to 8.

13. A pharmaceutical dosage form produced by selective laser sintering of a sintered powder, wherein the sintered powder comprises at least one active pharmaceutical ingredient and polyvinyl alcohol having a degree of hydrolysis of 70% to 90% and a viscosity of a 4% solution at 20°C of 3 to 8 mPas.

14. The pharmaceutical dosage form according to claim 13, wherein the degree of hydrolysis of the polyvinyl alcohol is 80% to 90% and the viscosity of a 4% solution at 20°C is 3 mPas to 4 mPas.

15. The pharmaceutical dosage form according to claim 13 or 14, wherein the sintered powder further comprises at least one light absorbing material.

Citation Information

Patent Citations

  • Controlled release tablet based on polyvinyl alcohol and its manufacturing

    WO2018083285A1